2019
DOI: 10.1007/s10346-019-01191-x
|View full text |Cite
|
Sign up to set email alerts
|

Engineering geomorphological investigation of the Kasavu landslide, Viti Levu, Fiji

Abstract: Rainfall-triggered landslides are prevalent along Fiji's main roads, but detailed studies of factors pre-conditioning slopes to fail and slope failure mechanisms are sparse. This study examines the factors leading to the Kasavu landslide, a small, shallow rotational landslide that transitioned into an earthflow along the Kings Road in Viti Levu, Fiji. The Kasavu landslide was triggered on 17-18 December 2016 by prolonged rainfall from a tropical depression. The extensive damage from the landslide resulted in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Of these, 219 TCs formed in the Bay of Bengal and 63 formed in the Arabian Sea. Tropical depressions are included in the statistics in this study, which explains the higher annual count compared with [18,19], because of their known impacts upon landfall, especially due to heavy rainfall [75,76]; Figure 3 shows the number of TCs that form in the NIO along with the number of TCs that make landfall at least once in the NIO over the 30-year period annually and by month. There is considerable inter-annual variability during the period of study, with peaks in activity approximately every 12 years, possibly corresponding to an unknown climatic signal.…”
Section: Tc Activity and Landfalling Trends In The North Indian Oceanmentioning
confidence: 99%
“…Of these, 219 TCs formed in the Bay of Bengal and 63 formed in the Arabian Sea. Tropical depressions are included in the statistics in this study, which explains the higher annual count compared with [18,19], because of their known impacts upon landfall, especially due to heavy rainfall [75,76]; Figure 3 shows the number of TCs that form in the NIO along with the number of TCs that make landfall at least once in the NIO over the 30-year period annually and by month. There is considerable inter-annual variability during the period of study, with peaks in activity approximately every 12 years, possibly corresponding to an unknown climatic signal.…”
Section: Tc Activity and Landfalling Trends In The North Indian Oceanmentioning
confidence: 99%
“…Landslides represent a common geohazard in many parts of the world and became a major concern to national and local authorities 1 , 2 . A large number of cases have been reported in many countries such as China, India, Vietnam, Japan 3 8 .…”
Section: Introductionmentioning
confidence: 99%
“…This study is essential because it adds knowledge and provide an understanding of the usefulness of ArcGIS and remote sensing analysis in Fiji Islands in solving complex issues of disaster risk reduction. Thus, several experts carried out research on landslide in Vitilevu Island, Fiji such Lawson [14], Howorth et al [15], Ram et al [16,19] and Greenbaum et al [17] revealed that rainfallinduced landslides are lethal for humanity.…”
Section: Introductionmentioning
confidence: 99%